What to do about the South African economy? - Aboobaker, Adam (New Agenda: South African Journal of Social and Economic Policy, 2024)
It goes without saying that in terms of economic performance South Africa is in dire straits. As many commentators have identified, per capita incomes have stagnated or fallen for over a decade, manufacturing – a sector of historical significance to long-term growth worldwide – has also fared poorly, and the disastrous state of key labor market indicators is known to all. It’s not only the state of the economy that leaves much to be desired; the state of economics commentary also needs to be strengthened through robust debate. Misgovernance and inappropriate policy choices have played a role in economic performance; there is and ought to be extensive conversation about this. For Duma Gqubule1 and several other commentators, the public deficit has been much too low, and it is possible to forecast (to one decimal point) macroeconomic outcomes if the ANC’s macro-policy choices were to persist after five or ten years of a possible coalition between the ANC and the center-right Democratic Alliance. A bigger deficit is seen to be a panacea.